1990
DOI: 10.1118/1.596475
|View full text |Cite
|
Sign up to set email alerts
|

Doses on the central axes of narrow 6‐MV x‐ray beams

Abstract: The absorbed doses on the central axes of narrow beams (radii 0.07-2.5 cm) of 6-MV x rays have been studied by experiments and Monte Carlo simulations. The measurements were made in a geometry used for irradiation of intracranial lesions. For radii less than 1.0 cm the dose on the central axis is progressively reduced due to electron disequilibrium. This leads to measurement artifacts when the detector is too large, as was readily observed with ionization chambers. Radiographic and radiochromic films were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 0 publications
5
70
0
2
Order By: Relevance
“…A Monte Carlo study described by Bjarngard et al 3 concluded that the detector size should be substantially smaller than the field size FIG. 16.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A Monte Carlo study described by Bjarngard et al 3 concluded that the detector size should be substantially smaller than the field size FIG. 16.…”
Section: Discussionmentioning
confidence: 98%
“…Several papers [1][2][3][4][5][6][7] have discussed measurement techniques for the small field beam data as well as dosimetric characteristics of MLC and mMLC. Those studies indicated that the measurement of dosimetric data for field sizes 12.5 mm or above could be relatively accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Acquisition of beam data for SRS and SABR can be particularly challenging, however, due to the small size of the fields employed and the partial volume effects associated with many common dosimeters. Further, small photon beams exhibit a loss of lateral electronic equilibrium on the central axis, producing output factors that falloff rapidly for fields below 10 mm in diameter 26 , 27 , 28 , 29 . Centering of the dosimeter in the beam is also challenging, and improper alignment of the beam and detector can introduce significant errors.…”
Section: Methodsmentioning
confidence: 99%
“…Difference of 3.7% from the calculated value is somewhat better than 14% smaller value of the stereotactic device of Im et al 8) Because of thicker plates and heavy materials, the device of Im et al 8) showed larger decrease in absolute dose measured at the center of the device. Furthermore, the PTW Model 31006 Pinpoint Chamber (PTW, Germany) with sensitive volume of 0.015 cm 3 is too small to measure absolute dose because of its small charge accumulation volume 1,3,15) . On the other hand, this chamber is too big to measure the absolute dose of the 4 mm helmet of Gamma Knife as Im et al did in their measurements.…”
Section: Discussionmentioning
confidence: 99%